Supporting Resilience in the Early Years - Walsh, Orla; Kane, John (International Journal of Practice-based Learning in Health and Social Care, 2015)
Resilience can be broadly defined as the ability to recover from setbacks, having protective qualities that lead to successful adaptation to life events (Mc Grath & Noble, 2011). A review of the literature indicates there are a growing number of programmes available internationally that aim to support resilience in children. However, these tend to be exclusively targeted at children from age 5 years and up. There is an absence both nationally and internationally of such programmes which focus directly on the very early years, i.e. 0-4 years. Semi-structured interviews were conducted with ECCE professionals to establish how they nurture resilience in practice. Findings indicate while many of the components that enhance resilience are present in early years settings, they are happening as an indirect consequence of other activities. We conclude that developmental psychology taught to ECCE students should be modified to include a greater focus on nurturing resilience in young children.